Apheresis in developing countries around the World. Issue 4 (27th October 2014) - Eichbaum, Quentin; Smid, W. Martin; Crookes, Robert; Naim, Norris; Mendrone, Alfredo; Marques, José Francisco Comenalli; Marques, Marisa B.
Abstract : At the combined American Society for Apheresis (ASFA) Annual Meeting/World Apheresis Association (WAA) Congress in San Francisco, California, in April of 2014, the opening session highlighted the status of apheresis outside of the United States. The organizers invited physicians active in apheresis in countries not usually represented at such international gatherings to give them a forum to share their experiences, challenges, and expectations in their respective countries with regard to both donor and therapeutic apheresis. Apheresis technology is expensive as well as technically and medically demanding, and low and median income countries have different experiences to share with the rest of the world. Apheresis procedures also require resources taken for granted in the developed world, such as reliable electrical power, that can be unpredictable in parts of the developing world. On the other hand, it was obvious that there are significant disparities in access to apheresis within the same country (such as in Brazil), as well as between neighboring nations in Africa and South America. A common trend in the presentations from Brazil, Indonesia, Malaysia, Nigeria, and South Africa, was the need for more and better physicians and practitioners' training in the indications of the various apheresis modalities and patient oversight during the procedures. As ASFA and WAA continue to work together, and globalization allows for increased knowledge‐sharing, improved access to apheresis procedures performed by qualified personnel with safety and high‐quality standards will be increasingly available. J. Clin. Apheresis 30:238–246, 2015. © 2014 Wiley Periodicals, Inc.